Perlakuan Akuntansi Terhadap Main Product dan By Product Serta Pengaruhnya Terhadap Laba Perusahaan (Studi Kasus Pada Pabrik Tahu dan Tempe Padang Tarok) - Dwi Anisa Pranata; Yefni Yefni; Heri Ribut Yuliantoro (Politeknik Caltex Riau, 2017)
The purpose of this research for to find out how the accounting treatment of main product and by product and to find out whether the sale of byproducts increase or decrease the company's profit Pabrik Tahu dan Tempe Padang Tarok. The accounting treatment in Pabrik Tahu dan Tempe Padang Tarok could do with 4 methods are: sales of by products are treated as other income, revenue of the product is recognized as an additional from sales revenue of main product, sales of by products is treated as a reduction to cost of goods sold. At the company's factory Tofu and Tempe using the method proceeds by products are treated as a reduction to cost of production. While to do the calculation of the main products and by-products using the market value method or methods grades reversal. In this method the main products and by-products are calculated and compared to the total number of its units during 2015. In the calculation of the market value method above can be seen the product cost per unit for products out of Rp50.696/ bowl at the point cut off, and Rp53.461/ basin after the cut off, whereas for products or crackers out of product cost per unit of Rp24.244/ kg. Therefore, sales by product increase its profit amounted to Rp146.950.680 ((30.000-24.244) x 25.530)).